Science teacher training: Jamaica - (Mission) June 1967 - June 1969 - Rudstrom, L. O.
This is a mission report on teacher training in science education and mathematics education in Jamaica, particularly inservice teacher training. It enlarges on the role of a proposed centre
Keywords: Mission reports